Pemberdayaan Keterampilan Berbicara Publik melalui Muhadhoroh di STIKK An-Nur II - Wahyu Divangga Tirta A; Muhammad Husni (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This Community Service Program (PKM) aims to improve students' public speaking skills and confidence through muhadhoroh activities at STIKK An-Nur II. Muhadhoroh was chosen because it was effective in training rhetoric and communication in the context of pesantren education.Mentoring is carried out with a qualitative descriptive approach through demonstration methods, lectures, video simulations, and hands-on practice. The subject of the program is students who need to strengthen rhetorical skills and have an interest in participating in muhadhoroh.The results of the activity showed an increase in speaking skills, material preparation, and the courage to appear in front of the audience. Students also show developments in language and expression aspects when giving speeches.Overall, these activities contribute to the formation of students' confidence and communication skills. Similar programs are recommended to be carried out on an ongoing basis as part of the development of student competencies in the pesantren environment.